Private sector promotion of climate-smart technologies: Experimental evidence from Nigeria - Liverpool-Tasie, Lenis Saweda; Dillon, Andrew; Bloem, Jeffrey R.; Adjognon, Guigonan Serge (International Food Policy Research Institute, 2022)
Sustainable intensification is predicated on climate-smart agricultural input adoption. We test strategies for promoting the adoption of climate-smart agricultural inputs in Nigeria with a private sector firm. We disentangle the effects of price discount promotions (25 percent discounts) relative to the firm’s standard “business as usual” marketing package. We find that the standard marketing package increases the adoption of climate-smart urea super granule (USG) fertilizer by 24 percentage points while reducing prilled urea utilization by 17 percentage points. Discounts increase adoption of USG by an additional eight percentage points, but are not profitable for the input supply firm as a scalable marketing strategy. Although treatment reduces nitrogen runoff damages valued between USD 43 and 113 per hectare, it did not lead to increased rice yields for farmers.